2013
DOI: 10.1080/ac.68.1.2959632
|View full text |Cite
|
Sign up to set email alerts
|

Survival and heart failure therapy in chronic dialysis patients with heart failure and reduced left ventricular ejection fraction: an observational retrospective study.

Abstract: After initiation of dialysis, patients with heart failure and reduced LVEF have a bad prognosis. Only a minority of these patients receive adequate specific heart failure treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Low left ventricular ejection fraction (LVEF) is associated with higher incidence of cardiovascular death in patients with non-dialysis-dependent CKD and in patients on dialysis. [4][5][6][7] The 3-year survival rate after CHF is 17% in patients on dialysis. 7 Cardiovascular disease (CVD) in CKD is treatable and potentially preventable and CKD appears to be a risk factor for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Low left ventricular ejection fraction (LVEF) is associated with higher incidence of cardiovascular death in patients with non-dialysis-dependent CKD and in patients on dialysis. [4][5][6][7] The 3-year survival rate after CHF is 17% in patients on dialysis. 7 Cardiovascular disease (CVD) in CKD is treatable and potentially preventable and CKD appears to be a risk factor for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Regression of LVM has also been shown to be associated with a more favorable outcome in this population (10). Studies on the natural course of LVM in patients with ESRD have reported stabilization or decrease of these measures over time (9,11), while the natural course of EF is to decrease slowly over time in this population (7,12).…”
Section: Introductionmentioning
confidence: 99%
“…LVM, EF, and PWV have all been repeatedly demonstrated to be relevant predictors of cardiovascular morbidity and mortality in patients with ESRD (5)(6)(7)(8)(9). Regression of LVM has also been shown to be associated with a more favorable outcome in this population (10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the subgroup of patients with a LVEF ≤30% the estimated HR for all‐cause and cardiovascular death increased to 3.45 (95% CI 1.71–6.94) and 12.39 (95% CI: 3.76–40.83), respectively. Accordingly, the HRs for all cause and cardiovascular death for patients with LVEF between 30% and 45% were 2.37 (95% CI 1.30–4.34) and 3.24 (95% CI 1.12–9.33), respectively . More recently, Yamada and co‐workers, evaluating the association of LVEF values and mortality in 1254 HD patients at the initiation of chronic HD, divided the patients into five groups according to LVEF levels with a decrease to 0.1 each (LVEF levels >0.6, 0.5 to 0.6, 0.4 to 0.5, 0.3 to 0.4, and <0.3) and followed up for up to 7 years.…”
Section: Discussionmentioning
confidence: 99%